Priming HIV Messages in Kenyan Print Media - Hezron Mogambi; Wambui Kiai; Ndeti Ndati (SAGE Open, 2013)
This paper is an investigation into the role of the print media in combating the HIV epidemic in Kenya. A critical analysis of how this information is covered is necessary to determine whether there is need for change of style in the presentation of this information . This is so because till date, there exists a gap in literature on how preventive knowledge on HIV is presented in the Kenyan print media. The data for this paper was gathered using both quantitative and qualitative designs. The paper relied mainly on the content analysis methodology in which the Daily Nation newspapers were searched for articles on HIV. The Daily Nation was purposively studied for this paper because it has the largest selling publication with the highest circulation and therefore, can adequately represent Kenya’s newspapers. All the issues of the year 2010 were purposively studied and this yielded a total of 365 copies for this paper. Findings of this paper indicate that the print media in Kenya lack consistency in the coverage of HIV issues. They also lack a clear editorial policy on the coverage of the epidemic that could guide in a sustained and effective method of coverage of the epidemic. Prominence of the HIV articles, which is a very crucial aspect in coverage, is also found to be lacking. This paper recommends that the print media should focus on consistency in their coverage… It is The print media should involve the general public, including people living with HIV in the discussion of the epidemic.